ENGLISH IN FOREIGN CHILDREN’S VIEW (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
In today’s interconnected world, English holds a unique position as the language of international communication, education, science, and culture. For children growing up in foreign countries, English is not just another subject in the curriculum; it serves as a gateway to a broader world, new opportunities, and personal development. The image of English in the eyes of foreign children reflects not only linguistic progress but also a shift in worldview, adaptability to global changes, and the creation of a shared cultural space that encompasses various backgrounds and identities.